Extraction, purification and preparation of species-specific phenolic glycolipid (PGL) from Mycobacterium bovis (AN5) - NAYAK, SUJIT; VERMA, RISHENDRA; KUMARI, NIRMALA; VENKATESAN, K (The Indian Journal of Animal Sciences, 2013)
Phenolic glycolipid (PGL) which is species-specific to Mycobacterium bovis AN5, was extracted, purified and deaeylatcd using preparative thin fayer chromatograpflY and florisitcolumn. On single directional chromatography, using sofvent system chloroform' methanol: water (90: 10: 1, v/v x 1), the mobility of deacylated PGl of M.bovis AN5 was identica wIth the mobility of authentic deacylated PGL (Rf value 0.23).